Effect of Local Simvastatin on the Healing of Surgically Created Critical-Sized Bone Defects: An experimental Study on sheep. - Rebin Azad Abdulsamad; Luqman Fawzi Omar (Erbil Dental Journal)
Background and objective: the role of simvastatin in lowering serum cholesterol levels is well described. However, recent findings suggest they have a role in bone formation as well. The study aims to determine the effect of local simvastatin application on bone defect healing and compare the amount of new bone produced by a simvastatin-treated defect with that produced by a bone graft (biphasic calcium phosphate) and non-treated defects (left empty) histologically.